Contact sensitivity and the DNA response in mice to high and low doses of oxazolone: low dose unresponsiveness following painting and feeding and its prevention by pretreatment with cyclophosphamide. - Asherson, G L (1979)
Cyclophosphamide was used to assess the role of suppressor cells in the contact sensitivity reaction. A single painting with 300 microgram and 30 microgram oxazolone produced poor contact sensitivity reactions (ear swelling). Cyclophosphamide (200 mg/kg) 2 days before painting increased the response to the lower doses but had less effect on the response to 3 mg oxazolone. A single feed with 10 mg oxazolone caused strong contact sensitivity while lower doses (10-1000 microgram) caused poor responses. Cyclophosphamide increased the response to the lower doses but not to the highest dose of oxazolone. These results suggested that the poor response to painting and feeding lower doses of oxazolone was due to a suppressor system which was sensitive to cyclophosphamide. A different result was obtained when contact sensitivity was measured by arrival of radioactively labelled cells. Cyclophosphamide had the greatest effect on cell arrival when high doses were fed. This indicates that ear swelling and cell arrival measure separate aspects of the contact sensitivity response. The lower doses of oxazolone, which caused little contact sensitivity, reduced the response to a standard immunizing dose. This low dose unresponsiveness occurred after either painting or feeding (Chase-Sulzberger phenomenon). It did not occur in mice treated with cyclophosphamide before the first exposure to oxazolone. This suggested that the low dose unresponsiveness was due to suppressor cells. The response to oxazolone was also assessed by DNA synthesis in the regional lymph nodes. A small dose of oxazolone (30 microgram) caused a peak of DNA synthesis on day four while a high dose (3 mg) caused a peak on day three. Pretreatment with cyclophosphamide depressed the response to 30 microgram although it increased contact sensitivity. The secondary response was smaller than the primary on days 3, 4 and 5 after immunization but larger on day two. The depression but not the increase was prevented by cyclophosphamide and was probably due to a suppressor system.